PENGARUH MEDIA PANLINTARMATIKA (PAPAN PERKALIAN PINTAR MATEMATIKA) TERHADAP MOTIVASI DAN HASIL BELAJAR MATERI PERKALIAN PADA SISWA KELAS II SD N 08 TIUMANG - Ratnawati; Dian Estu Prasetyo; Liza Fitri (STKIP Subang, 2024)
This research is motivated by mathematics learning which is still not optimal. The learning process does not use interesting media. Therefore, many students' motivation and learning outcomes are below the minimum completeness criteria. For this reason, researchers conducted research using panlintamatika media (mathematics multiplication board). The aim of this research was to determine the effect of panlintarmatics media (math smart multiplication board) on student learning outcomes in mathematics content unit 1 multiplication 2, subunit 11 multiplication number 2 at SD N 14 PULAU PUNJUNG and SD N 08 TIUMANG. This type of research is True Experimental Design with the form of Posttest Only Control Design. This research is divided into 2 groups, namely the experimental group and the control class. The research instruments used were multiple choice questions and questionnaires for learning motivation. The data collection technique used was posttest (final results). With the help of the SPSS 29 program using the Shapiro-Wilk test, with the criterion that if the results are significant, the results are greater than 0.05, meaning they are distributed. normal. Meanwhile, if the significant result is smaller than 0.05, it means it is not normally distributed. The results of this research show that there is an influence of learning from Panlintarmatics media (smart math multiplication board) on students' motivation and learning outcomes in multiplication material in class II of SD N 14 PULAU PUNJUNG and SD N 08 TIUMANG. This is proven by the posttest average